2002
DOI: 10.1002/oti.153
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapists' assessments of adults with long‐term pain: the Swedish experience

Abstract: The purposes of this study were to describe the needs for occupational therapy among people of working age with long-term pain, and to describe treatment interventions based on these assessments. Occupational therapists working in primary health care and/or with special interest in pain management (n=109) assessed 113 people aged 18-58 years with long-term pain with the Occupational Therapy Needs Assessment--Pain (OTNA--P) questionnaire. The occupational therapists recommended treatment interventions where app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 46 publications
1
17
0
8
Order By: Relevance
“…Results from this and other studies suggest that aspects of psychological wellbeing and psychosocial functioning must be addressed together with occupational performance [29] and that improvements in performance and satisfaction with performance are associated with increased self-efficacy and improved observed performance [28]. Accordingly, promoting self-management and teaching positive strategies seem to be effective for long-term pain patients, which is supported by our study as well as other studies [30,41]. A multidisciplinary pain management program should address the multiple factors that influence pain management and coping skills [42], where the key to success is considered to be based on ongoing communication between team members and the patient [43].…”
Section: Csupporting
confidence: 86%
“…Results from this and other studies suggest that aspects of psychological wellbeing and psychosocial functioning must be addressed together with occupational performance [29] and that improvements in performance and satisfaction with performance are associated with increased self-efficacy and improved observed performance [28]. Accordingly, promoting self-management and teaching positive strategies seem to be effective for long-term pain patients, which is supported by our study as well as other studies [30,41]. A multidisciplinary pain management program should address the multiple factors that influence pain management and coping skills [42], where the key to success is considered to be based on ongoing communication between team members and the patient [43].…”
Section: Csupporting
confidence: 86%
“…In a previous study, occupational therapists rated their patients' need for occupational therapy [40] using a slightly different version of the assessment instrument (OTNA -P) than used in the present study (OTNA -PP). Occupational therapists and persons with long-term:recurrent pain differed with regard to what needs:problems were reported most frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The rst questionnaire, OTNA -PP, is intended for use by persons with long-term:recurrent pain to assess self-perceived needs for occupational therapy (Appendix 1). It includes 19 items, of which one concerns the location of pain (item 1b) and one whether the respondent has ever been referred to occupational therapy (item 19), both with a yes:no for assessing cancer patients' need for occupational therapy [44,45] and on literature reviews concerning pain and occupational therapy in pain management [2,40]. The OTNA -P was used in a previous study [40], where signi cant correlations were found between patients' needs:problems as judged by occupational therapists and interventions in occupational therapy suggested by the occupational therapists.…”
Section: Subjects and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations